Influenza Virus Polymerase Mutation Stabilizes a Foreign Gene Inserted into the Virus Genome by Enhancing the Transcription/Replication Efficiency of the Modified Segment - Furusawa, Yuri; Yamada, Shinya; da Silva Lopes, Tiago Jose; Dutta, Jayeeta; Khan, Zenab; Kriti, Divya; van Bakel, Harm; Kawaoka, Yoshihiro (mBio, 2019)
The reverse genetics method of influenza virus generation has enabled us to generate recombinant viruses bearing modified viral proteins. Recombinant influenza viruses expressing foreign genes have become useful tools in basic research, and such viruses can be utilized as efficient virus vectors or multivalent vaccines. However, the insertion of a foreign gene into the influenza virus genome often impairs virus replication, and the inserted genes are unstable. Elucidation of the mechanisms of foreign gene stabilization will help us to establish useful recombinant influenza viruses. We previously attempted to establish a reporter influenza virus by inserting the gene for the Venus fluorescent protein into the NS segment of influenza A/Puerto Rico/8/34 (PR8, H1N1) virus to yield WT-Venus-PR8. Although the inserted Venus gene was deleted during serial passages of WT-Venus-PR8, we discovered that the PB2-E712D mutation stabilizes the Venus gene. Here, we explored the mechanisms by which Venus gene deletion occurs and how the polymerase mutation stabilizes the Venus gene. Deep sequencing analysis revealed that PB2-E712D does not cause an appreciable change in the mutation rate, suggesting that the stability of the Venus gene is not affected by polymerase fidelity. We found by using quantitative real-time PCR that WT-Venus-PR8 induces high-level interferon beta (IFN-β) expression. The induction of IFN-β expression seemed to result from the reduced transcription/replication efficiency of the modified NS segment in WT-Venus-PR8. In contrast, the transcription/replication efficiency of the modified NS segment was enhanced by the PB2-E712D mutation. Loss of the Venus gene in WT-Venus-PR8 appeared to be caused by internal deletions in the NS segment. Moreover, to further our understanding of the Venus stabilization mechanisms, we identified additional amino acid mutations in the virus polymerase complex that stabilize the Venus gene. We found that some of these amino acids are located near the template exit or the product exit of the viral polymerase, suggesting that these amino acids contribute to the stability of the Venus gene by affecting the binding affinity between the polymerase complex and the RNA template and product. IMPORTANCE The reverse genetics method of influenza virus generation has enabled us to generate recombinant viruses bearing modified viral proteins. Recombinant influenza viruses expressing foreign genes have become useful tools in basic research, and such viruses can be utilized as efficient virus vectors or multivalent vaccines. However, the insertion of a foreign gene into the influenza virus genome often impairs virus replication, and the inserted genes are unstable. Elucidation of the mechanisms of foreign gene stabilization will help us to establish useful recombinant influenza viruses.